AN AN AUDIT IMPLEMENTATION PROCEDURES FOR ACCOUNT RECEIVABLE AT PT XYZ BY YANISWAR PUBLIC ACCOUNTANT AND PARTNER - Fadhlil Azhim Alda; Elsa Fitri Amran; Elfina Yenti (UIN MAHMUD YUNUS BATUSANGKAR, 2025)
This study aims to analyze the procedures for auditing accounts receivable at PT XYZ conducted by KAP Yaniswar and Rekan Pekanbaru, with particular emphasis on compliance with Auditing Standards (SA) 300, SA 315, SA 320, SA 330, and SA 505. The research employs a descriptive qualitative approach using interviews, observations, and documentation techniques. The findings indicate that the audit process was carried out systematically, encompassing audit planning, risk assessment, substantive testing, and external confirmation, and was supported by a layered audit quality control system involving review by junior auditors, supervisors, and audit partners. Although the overall implementation of the audit procedures complied with the applicable Auditing Standards and provided reasonable assurance regarding the fairness of accounts receivable balances, this study identifies certain limitations, particularly in the depth of risk analysis and the suboptimal response rate to external confirmations. Therefore, this study recommends strengthening the risk-based audit approach and enhancing the effectiveness of external confirmation procedures to improve audit quality, especially within small and medium-sized public accounting firms.